Factors associated with body mass index changes among older adults: a ten-year follow-up - Tânia Aparecida de Araujo; Ligiana Pires Corona; Flavia Cristina Drumond Andrade; Manuela de Almeida Roediger; Yeda Aparecida de Oliveira Duarte
To examine changes in body mass index (BMI) among older Brazilian adults and associated factors. Longitudinal, population-based study, conducted in São Paulo, Brazil. Adults aged 60 years or over (n = 1,796) from the first wave of data collection from the Health, Well-Being, and Aging Study (SABE Project) conducted from 2000 to 2010. Repeated mixed-effects linear regression was used to analyze longitudinal changes in BMI and to examine whether sociodemographic characteristics, health conditions, and social behaviors were associated with these changes. Mean BMI decreased after 70 years. Men had lower BMI than women (β = -1.86, 95%CI: -2.35; -1.37). Older adults who consumed alcohol (β = 0.30, 95%CI: 0.06; 0.54), had more than one chronic disease (β = 0.19, 95%CI: 0.26; 0.72) and who did not perform physical activity (β = 0.56, 95%CI: 0.38; 0.74) had higher BMI. Subjects who smoked (β = -0.40, 95%CI: -0.76; -0.04) and who reported having eaten less food in recent months (β = -0.48, 95%CI: -0.71; -0.24) had lower BMI. In older Brazilians, several sociodemographic characteristics, health conditions, and behaviors predict BMI. Increasing prevalence of chronic diseases and growing sedentary behaviors in Brazil may have detrimental effects on BMI at older ages.